Socio-economic and environmental factors affecting the rehabilitation of children with severe malnutrition - Felliyani Felliyani; Sri S Nasar; Taralan Tambunan (Indonesian Pediatric Society Publishing House, 2016)
Background Poor diet and high infection rates inflicted by low socio-economic status and poor environments among infants and young children appear to be major causes of severe malnutrition. Objective To determine the practical and likely effectiveness in rehabilitation of severe malnutrition. Methods A descriptive observational study was conducted on 27 children at three different sites: (1) Five inpatients at the Inpatient Ward, Cipto Mangunkusumo Hospital, Jakarta (IP-CM); (2) 8 out- patients at the Metabolic and Nutrition Clinic, Cipto Mangunkusumo Hospital (OP-CM); (3) 14 outpatients at the Nutrition Clinic, Bogor (NC). All the patients followed were aged <60 months and suf- fered from severe malnutrition (weight for length index <-3 NCHS Z-score). Subjects were followed for 12 weeks. The IP-CM group received standard treatment following the WHO recommendation, while the OP-CM and NC group received proper medical treat- ment and nutrition education for mothers. The OP-CM group un- derwent more extensive laboratory investigations. Results All children generally had low socio-economic status. Most children experienced poor feeding, child care, and other health practices. A tendency of increased prevalence, number of episodes, and duration of infectious diseases was noted in the majority of subjects. However, an improvement of nutritional status was ob- served during treatment in all groups, particularly in the IP-CM group. Conclusion Socio-economic status and environmental factors must be considered in the management of severe malnutrition. Educating parents concerning proper feeding and child care prac- tices appears to be of permanent nutritional benefit for the chil- dren.